Coping With Governmental Restrictions: The Relationship Between Stay-at-Home Orders, Resilience, and Functional, Social, Mental, Physical, and Financial Well-Being - Barrett, Adriana M.; Hogreve, Jens; Brüggen, Elisabeth C. (Frontiers in Psychology, 2021)
The coronavirus outbreak has led to abrupt changes in people’s daily lives as many state governments have restricted individuals’ movements in order to slow the spread of the virus. We conducted a natural experiment in the United States of America in April 2020, in which we compare responses from states with “stay-at-home orders” (3 states) and no such orders (6 states). We surveyed 458 participants (55.6% female, age range 25–64, Mage = 36.5) and examined the effects of these government-imposed restrictions on social, mental, physical, and financial well-being as well as the mediating role of resilience. Structural equation modeling reveals that resilience buffers stay-at-home orders’ potential side-effects on well-being. Specifically, individuals living in states with stay-at-home orders report lower functional well-being than individuals living in states without such orders, which negatively relates to resilience. Resilience in turn is associated with higher social, mental, physical, and financial well-being. Thus, resilience can be seen as an effective means of buffering stay-at-home orders’ potential negative effects on the components of well-being. Our results indicate the central role of resilience, which is crucial in dampening the effects of stay-at-home orders on well-being. Following our results, governments and policymakers should focus their efforts on strengthening individuals’ resilience, which is a key predictor of social, mental, financial, and physical well-being.